Directions and Opportunities in Health Informatics in British Columbia - Thornton, K. (Methods of Information in Medicine, 1994)
The social changes, and changes in perceptions of the effectiveness of health care in British Columbia have resulted in a large number of recommendations in the report of the British Columbia Royal Commission on Health Care and Costs. Many of these recommendations have implications for health informatics. The British Columbia Government, in outlining a response, foresees a major change in the emphases of health care, which will involve four major areas of health informatics: network evolution, automation of the patient record, outcome- and other quality-related databases, and consumer health education. These themes are discussed, in the light of the opinions of academics, health care providers, and the health-informatics industry. The themes must be intercalated into the health informatics curriculum, to equip graduates for the challenges of B.C.’s changing health care system.
Keywords: Health Care Structure; Community Care